ENGAGING STUDENT-RESEARCHERS IN WRITING UP RESEARCH PROJECT PROPOSAL: PARTICIPATORY ACTION RESEARCH - Merdeka, Bagus Muhamad Ikrar Tegas; Ramdani, Junjun Muhamad; Rahmat, (ENGLISH JOURNAL, 2025)
In the last decade, Community of Practice (CofP) theory has been myriad investigated in some different contexts. However, in the educational field, it still remains sparsely to investigate this concept applied as a method in an EFL context to engage students in a research proposal project. To fill this gap, this participatory action research (PAR) attempts to examine the way of a CofP engages the students in writing up a research project proposal in English education department. Five recruited participants of the student teachers who follow a CofP were observed. The data were collected by using interview and photographs. The photographs were analysed by using SHOWED analysis (Wang, 1999). Then, the whole data were analysed thematically (Braun & Clarke, 2006). The results showed that the students in CofP were engaged in writing a proposal by (1) writing proposal as a shared domain, (2) members’ relationship in student-researcher club (SRC), and (3) joint activities in SRC. This study provides the empirical insights into the contributions of CofP toward student-researchers’ proposal writings.